Constructivism and the new social studies : a collection of classic inquiry lessons - Scheurman, Geoffrey; Evans, Ronald W. (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"The New Social Studies refers to a flurry of academic and commercial activity during the 1960s and 1970s that resulted in the mass development and dissemination of revolutionary classroom materials and teacher resources. In science as well as social studies, a spirit of 'inquiry-based teaching' filled the air during this time, resulting in the development of curricula that were both pedagogically innovative and intellectually rigorous. 'Constructivism and the New Social Studies' contains a collection of classic lessons from some of the most successful projects of the era, providing a resource of exceptional ideas and materials that have stood the test of time. These revealing artifacts are presented with commentaries from some of the original directors of major projects, including Edwin Fenton, Barry Beyer, and Suzanne Helburn. In addition to American and World History, groundbreaking lessons are represented in Economics, Government, Sociology, and Geography, including the Public Issues Series (Fred Newann) and Man: A Course of Study (Peter Dow). With a Foreword by Jerome Bruner, the volume not only provides a resource of exceptional curriculum ideas and actual materials that have stood the test of time. It also builds a lucid bridge between the theoretical ideas of constructivism and the pedagogical principles of inquiry learning"-- Provided by publisher.
Keywords: Social sciences -- Study and teaching.; Constructivism (Education); Education -- Teaching -- Subjects -- Social Science.; Constructivism.; Teaching of a specific subject.; Educational: Social sciences, social studies.; elektronické knihy; electronic books